Application of Ammonium Persulfate for Selective Oxidation of Guanines for Nucleic Acid Sequencing - Yafen Wang; Chaoxing Liu; Tingting Hong; Fan Wu; Shuyi Yu; Zhiyong He; Wuxiang Mao; Xiang Zhou (Molecules, 2017)
Nucleic acids can be sequenced by a chemical procedure that partially damages the nucleotide positions at their base repetition. Many methods have been reported for the selective recognition of guanine. The accurate identification of guanine in both single and double regions of DNA and RNA remains a challenging task. Herein, we present a new, non-toxic and simple method for the selective recognition of guanine in both DNA and RNA sequences via ammonium persulfate modification. This strategy can be further successfully applied to the detection of 5-methylcytosine by using PCR.